Peningkatan Phbs Melalui Edukasi Bahaya Merokok, Pengelolaan Sampah, Dan Cuci Tangan Di Pesantren Maslahatul Ikhwan - Rijal Maulana Juan Alkautsar; Rizki Gifari Pratama; Hilda Tri Afia Damayanty S; Reka Indah Lestari; Susi Wahyuning Asih (Utami Publisher, 2026)
The implementation of Clean and Healthy Living Practices (PHBS) in Islamic boarding schools is a crucial step toward minimizing the risk of disease and improving the health of students. According to the results of the Indonesian Health Survey (SKI), the prevalence of daily smoking among adolescents aged 10–18 in East Java reached 5.3%, while occasional smoking stood at 2.6%. The rate of proper handwashing compliance is only 58.4%, accompanied by suboptimal waste management practices, such as open burning of waste (65.8%). These conditions underscore the urgency of strengthening PHBS education programs. The approaches implemented included: (1) lecture sessions presenting core material, and (2) brainstorming techniques that encouraged active participant engagement in sharing perspectives on the material. Educational videos were selected as supporting media due to their ease of use and ability to present visual and narrative information that is more engaging and easily digestible. Pre-intervention evaluations indicated that the majority of students fell into the “adequate” (40.5%) and “inadequate” (32.4%) categories. Following the intervention—which included lectures, discussions, and demonstrations—the proportion in the “good” category surged to 59.5%, with the “poor” category disappearing entirely. It can be concluded that the health education intervention proved effective in improving PHBS practices among boarding school students.